Implementation of Academic Supervision in Developing Teacher Competence and Work Motivation to Improve Performance: A Case Study at SMA Negeri 7 Pekanbaru - Yuda Fransiska; Maya Novita Sari (Journal of Educational Sciences, 2026)
This study investigates the implementation of a data-driven academic supervision model anchored in school education report card recommendations and its integrated impact on teacher competence, work motivation and performance at SMA Negeri 7 Pekanbaru. Unlike prior studies that examined supervision in broader contexts, this research offers a single-case, in-depth analysis that traces specific supervision outcomes. A qualitative case study approach was employed using semi-structured interviews with eight key informants, supported by classroom observation and document analysis. Data were analyzed using the Miles et al. (2014) interactive model, with validity ensured through source and technique triangulation and member checking. Findings reveal that structured Supervision encompassing pre-conference, classroom observation, and post-conference stages measurably improved teacher competence, evidenced by enhanced HOTS-based assessment design and adoption of inquiry and project-based learning; sustained high work motivation, reflected in consistent monthly attendance and active MGMP participation; and strengthened teaching performance, demonstrated through institutionalized reflective teaching journals and diversified instructional methods. Post-supervision follow-up continuity remains a key challenge. The study concludes that systematic, constructive academic supervision significantly enhances teacher professional competence, work motivation and overall teaching performance.